Fruit recognition system using color filters and histograms - Budi Sugandi; Rahmi Mahdaliza (ILKOM Jurnal Ilmiah, 2021)
Nowadays, many children and adults do not know the type or name of fruits, especially if the fruit is a rare one. In this paper, a system was developed that can recognize fruit names in real time using a camera as a visual sensor. The camera captured the image and processed using image processing. This paper proposed a method using HSL color filters, RGB histograms and shapes of fruit objects to detect and recognize fruits. The proposed method was divided into two processes, namely the training and testing processes. The training process was carried out to obtain a database of each fruit. The first process of training was object detection using an HSL color filter. The calculation of the RGB histogram was conducted on the HSL color filtered object. After that, the object's roundness was measured. Meanwhile, the testing process was done by looking for the similarity of the histogram data of the test object with the reference object by using the histogram distance equation. The similarity of the object was determined by the distance value of the histogram of the tested fruit with the referenced fruit. Similar objects would have histogram distances less than the threshold values. Tests were implemented in several types of fruit. The test results showed the system could recognize fruit names accurately.